THE ROLE OF THE TEACHER IN DEVELOPMENT BEGINNING READING ABILITY CLASS II STUDENTS OF SDK GAPONG ACADEMIC YEAR 2021/2022 - Fransiska Jaiman Madu; Maria Hariyati (PGSD UNIKA SANTU PAULUS RUTENG, 2023)
This research was motivated by the low reading ability of grade II students at SDK Gapong. This relates to the ability of the teacher in develop students' reading ability. This research aims to explain the role of the teacher in developing the reading skills of grade II students at SDK Gapong for the 2021/2022 academic year. As for type study Which used is qualitative with t data collection technique use interview, observation, and documentation. The steps used in analyzing the data are data collection, data reduction, data presentation, and drawing conclusions. Results study show that the role of the teacher in developing students' reading skills as following. First, Teacher as an educator, meaning that the teacher trains the skills, attitudes, and mentality of students, as well as sets a good example for students. Second, the teacher as a teacher, efforts made as a teacher to provide knowledge to students. Third, the teacher as a resource study, namely providing learning material by introducing story-telling media to students. Fourth, the teacher as a facilitator, should always provide learning facilities to students as a support for the learning process of reading. Fifth, the teacher as a guide, give directions for good reading. Sixth, the teacher as a demonstrator, shows learning steps with various strategies that are easy to understand. Seventh, the teacher as manager, namely managing students in creating a comfortable atmosphere. Eighth, the teacher as an adviser, the teacher solves all the problems of students' reading difficulties. Ninth, the teacher as a motivator, namely the teacher gives reinforcement to students. Tenth, the teacher as a trainer, provide reading practice to students. Eleventh, the teacher as an innovator, able to create new learning models. Twelve, the teacher as evaluator, namely the teacher conducts an assessment through tests and non-tests.